A framework for risk mitigation in halal self-declaration for SMEs and MSMEs in Indonesia / Firdaus Fanny Putera Perdana and Ahmad D. Habir - Putera Perdana, Firdaus Fanny; D. Habir, Ahmad (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
This research examines the challenges and risk mitigation strategies associated with Halal self-declaration among Small and Medium-sized Enterprises (SMEs) and Micro, Small, and Medium-sized Enterprises (MSMEs) in the context of the forthcoming Halal certification enforcement policy in Indonesia. The study aims to enable SMEs and MSMEs to actively participate in the Halal industry, with the intent to promote economic inclusivity and ensure the accuracy, integrity, and reputation of Halal products. The research explores potential consequences such as mislabeling, cross-contamination, reputational damage, legal repercussions, negative market impact, and erosion of Halal industry credibility. In this research, a structured thematic analysis approach is conducted. The findings of the study propose risk mitigation strategies, including risk identification, framework development, education programs, accessible guidance materials, the implementation of independent verification and audits collaboration with certification bodies and regulatory agencies, awareness campaigns, and continuous improvement and evaluation. The outcomes of this research benefit SMEs, MSMEs, certification bodies, industry associations, regulatory agencies, and consumers, enhancing compliance with Halal standards, consumer confidence, and market competitiveness.